Penerapan Pendekatan Contextual Teaching and Learning (CTL) untuk Meningkatkan Keterampilan Berpikir Kreatif dan Kemandirian Belajar Siswa pada Pembelajaran PAI di Sekolah Dasar Kecamatan Leuwiliang Kab.Bogor - Rismawati; Chaira Saidah Yusrie; Yusi Srihartini (Jurnal Dirosah Islamiyah, 2024)
This study is motivated by challenges in Islamic Religious Education (PAI) learning at the elementary school level, such as teachers' difficulty in connecting religious teachings to students' real-life situations, as well as limitations in media and infrastructure. Low student learning independence and a lack of creative thinking skills are also major focuses. The aim of this study is to explore the application of the Contextual Teaching and Learning (CTL) approach to enhance students' creative thinking skills and learning independence in PAI learning at elementary schools in Leuwiliang District, Bogor Regency. The method used is descriptive qualitative, with data collected through interviews, observations, and documentation. The results show that the application of CTL significantly improves students' creative thinking skills, such as the ability to think originally, flexibly, and fluently. CTL has also proven effective in enhancing learning independence, marked by increased student initiative in managing their own learning. Supporting factors include teacher creativity and technological support, while inhibiting factors involve the limitations of learning media and school facilities. This study provides theoretical contributions to the PAI learning model through CTL, as well as practical implications for teachers and stakeholders in improving the quality of learning in elementary schools. Keywords: Contextual Teaching and Learning (CTL), creative thinking skills, student learning independence.